2023
DOI: 10.1007/jhep03(2023)119
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear stability of α′-corrected Friedmann equations

Abstract: We study the non-linear stability of fixed-point solutions to the α′-exact equations from O(d, d) invariant cosmology, with and without matter perturbations. Previous non-linear analysis in the literature is revisited, and its compatibility with known linear perturbation results is shown. Some formal aspects of cosmological perturbations in duality invariant cosmology are discussed, and we show the existence of time-reparameterization invariant variables for perturbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In [158,163] solutions of the equations of motion of DFT cosmology from [153,154] coupled to matter obeying the T-duality symmetry were analyzed., and their stability was studied [163]. 6 In [159] (see also [167,168]) it was shown that the formalism of [153,154] (including matter) can be generalized to an anisotropic setting. In particular, we can consider a setup in which matter is initially dominated by winding modes about all spatial dimensions and then undergoes a phase transition in which the winding modes about three (external) dimensions decay into radiation while those about the other six (internal) dimensions persist, as argued to be the case in String Gas Cosmology.…”
Section: Jcap11(2023)019mentioning
confidence: 99%
“…In [158,163] solutions of the equations of motion of DFT cosmology from [153,154] coupled to matter obeying the T-duality symmetry were analyzed., and their stability was studied [163]. 6 In [159] (see also [167,168]) it was shown that the formalism of [153,154] (including matter) can be generalized to an anisotropic setting. In particular, we can consider a setup in which matter is initially dominated by winding modes about all spatial dimensions and then undergoes a phase transition in which the winding modes about three (external) dimensions decay into radiation while those about the other six (internal) dimensions persist, as argued to be the case in String Gas Cosmology.…”
Section: Jcap11(2023)019mentioning
confidence: 99%